The Impact of Food Chemical Composition on the Absorption of Vitamins and Minerals in the Human Body - Narges Teimoory; Ghullam Mahboob Ahmadi (Cleanliness: Journal of Health Sciences and Medical Research, 2025)
The absorption of vitamins and minerals from food is a critical factor influencing human health and nutrition. This literature review examines how the chemical composition of food including naturally occurring inhibitors and enhancers affects the bioavailability of essential micronutrients. Emphasis is placed on the role of compounds such as phytates, oxalates, tannins, and polyphenols in reducing absorption, as well as the enhancing effects of vitamin C, dietary fats, heme iron, organic acids, and specific amino acids. Understanding these interactions provides insight into optimizing nutrient uptake through dietary choices, traditional food preparation methods, and targeted public health strategies.